Modification of the active centre of nattokinase to enhance its thermostability using a strategy based on molecular dynamics simulation, steered dynamics simulation, and conservative prediction - Li, Yuan; Zhu, Wenhui; Chen, Liangqi; Tang, Xiyu; Ma, Aixia; Ma, Yuwei; Li, Tongli; Li, Xingrui; Ma, Ye; Li, Jinyao (Frontiers in Nutrition, 2024)
The poor thermostability of nattokinase represents a significant limitation in its potential applications. Additionally, there is a notable absence of studies focused on modifying residues within the active site region of nattokinase with the aim of enhancing its catalytic properties. Furthermore, the direct utilisation of directed evolution often yields unfavourable outcomes, with a considerable workload being a common consequence. In this study, a novel combined approach was proposed, based on molecular dynamics simulation, steered dynamics simulation and conservative analysis with site-directed mutagenesis, with the aim of addressing the aforementioned issue. Based on these findings, the mutant A216K was selected for a 5.7-fold increase in half-life at 55°C with a small increase in activity, which further enhanced the mutation library of the thermal stability enhancement site in the enzyme's active centre. We also used molecular dynamics simulations to elucidate the mechanism by which three mutants of 216 amino acid residues (A216E, A216K and A216R) increase the thermostability of nattokinase. It is anticipated that this strategy will provide novel insights into enzyme engineering research.